2021
DOI: 10.3389/fspor.2021.670263
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning to Improve Orientation Estimation in Sports Situations Challenging for Inertial Sensor Use

Abstract: In sports, inertial measurement units are often used to measure the orientation of human body segments. A Madgwick (MW) filter can be used to obtain accurate inertial measurement unit (IMU) orientation estimates. This filter combines two different orientation estimates by applying a correction of the (1) gyroscope-based estimate in the direction of the (2) earth frame-based estimate. However, in sports situations that are characterized by relatively large linear accelerations and/or close magnetic sources, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Along with the various experimental environments, a wide variety of measurement systems were used, from optoelectronic motion capture systems to IMUs, EMGs, pressure sheets, video cameras, force plates and instrumented wheels; each coming with its own pros and cons. For instance, IMUs allow to overcome the spatial restriction imposed by optoelectronic motion capture systems, enabling field measurements, but are less accurate to assess body orientation ( 81 ). Ideally, beyond their level of accuracy, measurement systems would not noticeably impact the subject's propulsion and the MWC characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the various experimental environments, a wide variety of measurement systems were used, from optoelectronic motion capture systems to IMUs, EMGs, pressure sheets, video cameras, force plates and instrumented wheels; each coming with its own pros and cons. For instance, IMUs allow to overcome the spatial restriction imposed by optoelectronic motion capture systems, enabling field measurements, but are less accurate to assess body orientation ( 81 ). Ideally, beyond their level of accuracy, measurement systems would not noticeably impact the subject's propulsion and the MWC characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in some cases, measuring forces might be redundant with the use of IMUs. For instance, in wheelchair propulsion, it might be possible to estimate rolling resistance by placing an IMU on the wheelchair and one on the trunk [ 30 ]. Force on the rear and caster wheels could be modelled as a function of trunk angle and in combination with coast down tests for rolling resistance coefficients, rolling resistance could be estimated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated the estimation of EAs with the application of inertial measurement units (IMU) at the back of the ski boots (Snyder et al, 2020). IMUs have many advantages over motion capture systems, as they are small, wearable, affordable and can easily be used outside the laboratory (van Dijk et al, 2021). While IMUs can be used to calculate the global orientation of objects they are attached to, the reference to the snow surface is more relevant to understand ski-snow interaction (e.g.…”
Section: Citationmentioning
confidence: 99%